Gli inibitori della pompa protonica nelle patologie acido correlate: il ruolo di rabeprazolo in una strategia di cost-minimisation - Colombo, Giorgio L.; Muzio, Andrea (Farmeconomia. Health economics and therapeutic pathways, 2003)
The clinical management of acid-related diseases incurs the consumption of a relevant part of the health resources in Italy, as indicated by the fact that PPIs (proton pump inhibitors) represented the first pharmacological class in terms of drug expenditures in 2002, making up 6,3% of the total. It’s therefore of primary importance to evaluate the economical consequences of their utilization, beyond the clinical outcomes. In the present article a cost-minimization analysis is performed, basing on drug consumption data and focusing on the new reference-price based criteria introduced by the Italian Ministry of Health for the reimbursement of pharmaceuticals. A model for the economical evaluation of the use of PPIs was developed, based on the assumption that all the active substances in this class share the same clinical benefit, and following a stepdown approach, in which the PPIs are administered full-dose for a month, followed by a one year maintenance period at half-dose. The model yielded the following results: rabeprazole is the most cost-saving drug of this class in the Italian setting, permitting important savings on an hypothetical 1.000 patient population, ranging from 13.000 euro, when compared to omeprazole, to 279.000 euro, if related to the most expensive substance, esomeprazole. In other terms, on the basis of the assumed equal effectiveness of the considered alternatives, the costs incurred for the treatment of 1.000 patients with esomeprazole would be sufficient to treat 1.769 patients with rabeprazole.